Shaping the World of Change : Higher Education as a Key Enabler - Broucker, Bruno,; Gannon, Anne,; Nooij, Jessica,; O'Hara, Mark,; Preymann, Silke, (Educational Research E-Books Online, Collection 2024., 2024)
This book sets out the theme of a world that is changing rapidly and higher education being an important agent in shaping that change through knowledge generation, transfer and innovation. The chapters in this book focus on this shaping role of higher education along a number of key areas: governance, sustainability, teaching and learning, student agency, quality and internationalization. From these different topics, this volume presents ways in which higher education helps dealing with and shaping the educational and societal changes that we are facing in the aftermath of the pandemic and challenges that we are expecting in the near future. Contributors are: Victor M. H. Borden, Bruno Broucker, Edel Cassar, Bárbara Coelho Gabriel, Cindy Cogswell, Julia Draghi, Brigitte Ecker, Pınar Eldemir, Klaus Feldmann, Cláudia Figueiredo, Anne Gannon, Jussi Kivistö, Manja Klemenčič, Theodor Leiber, Nandarani Maistry, Sara Moreno Pires, Takalani Muloiwa-Klenam, Darlington Mutakwa, Erna Nairz-Wirth, Ruaidhri Neavyn, Jessica Nooij, Mark O'Hara, Beate Pawle, Alexandra Polido, Maria Pöschl, Silke Preymann, Verena Régent, Lotte Scheeren, Kateryna Suprun, Robertt Valente, Floris J. N. van Berckel Smit, Annemieke van der Horst and Sabine Weiss.